Impact of temperature-controlled endobiliary radiofrequency ablation for inoperable hilar cholangiocarcinoma: A propensity score–matched analysis - Shin, Il Sang; Moon, Jong Ho; Lee, Yun Nah; Myeong, Jun Ho; Lee, Tae Hoon; Yang, Jae Kook; Cho, Young Deok; Park, Sang-Heum (Endoscopy International Open, 2024)
Background and study aims Endobiliary radiofrequency ablation (RFA) can be an effective palliative treatment, but few studies have evaluated its outcomes for malignant obstruction in the hilar bile duct, which has a thin wall and complex duct–vascular contacts. We evaluated the efficacy and safety of temperature-controlled endobiliary RFA, which can reduce the risk of unintentional thermal injury by maintaining the temperature of the ablation segment, in the treatment of inoperable hilar cholangiocarcinoma (CCA).Patients and methods After propensity score matching, 64 patients with inoperable hilar CCA were categorized to the RFA + stent group (endobiliary RFA with stenting; n=32) or stent-only group (stenting only; n=32). The evaluated outcomes were the median time to recurrent biliary obstruction (RBO), overall survival (OS), and adverse events (AEs).Results Technical success was achieved in all patients. The clinical success rate was 93.8% in the RFA + stent group and 87.5% in the stent-only group (P=0.672). The median time to RBO was 242 days in the RFA + stent group and 168 days in the stent-only group (P=0.031). The median OS showed a non-significant tendency to be higher in the RFA + stent group (337 versus 296 days; P=0.260). Overall AE rates were comparable between the two groups (12.5% vs 9.4%, P=1.000).Conclusions Temperature-controlled endobiliary RFA resulted in favorable stent patency without increasing the rate of AEs but it did not significantly increase OS in patients with inoperable hilar CCA (Clinical trial registration number: KCT0008576).
Keywords: Pancreatobiliary (ERCP/PTCD); ERC topics; Strictures